Microwave-assisted synthesis of lanthanide-based calcium fluoride nanoparticles for luminescent applications - De Silva, C.R. (University of Jaffna, 2022)
Nanotechnology deals with materials in the nanometer size range and promises future applications in biomedical sciences. Among the metal-based nanomaterials, calcium fluoride has received recent attention in biomedical sciences due to its limited toxicity, biocompatibility, and stability. In addition, lanthanide-based fluoride nanoparticles exhibit impressive luminescent properties, including narrow luminescent bands, longer luminescent lifetimes, large Stokes shifts, and limited photo-bleaching. Recent methods of making calcium fluoride nanoparticles include co-precipitation, hydrothermal, microemulsion, and sol–gel processes. Notwithstanding the current progress, it is essential to develop reproducible synthetic methods for making high quality nanoparticles with improved monodispersity. Herein, we introduce a microwave-assisted synthetic method for making europium-doped calcium fluoride nanoparticles with high reproducibility, colloidal stability, and monodispersity. Powder X-ray diffraction studies confirmed that the nanoparticles have a cubic structure. The europium doping levels (1−35 %) did not significantly alter the crystal structure of calcium fluoride. Transmission electron microscopy images confirm the production of highly monodispersed nanoparticles with a flower-like structure and a rough surface. The size of the nanoparticles can be varied between 40 – 1000 nm by changing the microwave conditions and the initial reactant concentration. The nanoparticles exhibit europium (III)-based luminescence at 615 nm with a full-width at half maximum of 15 nm upon 340 nm excitation. A luminescent quantum yield of 1.5 % was observed with 15 % europium doping. Optimization of the luminescent efficiency by a surface engineering process is in progress.
Keywords: Calcium fluoride; Nanoparticles; Lanthanide; Nano-synthesis; Luminescence